Analysis of the concep of induction - Vásquez Tasayco, Alberto (2014)
The article begins by specifying the concepts of reason and thought, needed in scientific activity. Then develop the basic ideas of Aristotle, who was concerned to provide the scientific construction methods. Methods, the important thing is what kind of conclusion lead. Thus, the deduction that uses the syllogism leads to true conclusions, but the induction was always a concern for the kind of real conclusion to which it leads. Concerns arise from the ancient Greeks, the medieval and modern on the induction, since the positions of logicians and philosophers. Similarly, the article focuses on the problem of justification of induction, logically speaking (Hume and Mill), but also in the justification as data gather process for building cognitive structures (Whewell). Induction was always criticized and even eliminated by Popper, but scientists in the natural sciences defend it in its methodological character, not by their ability demonstrative. Finally, we present findings on the induction and the Michelson-Morley.